A prospective randomized trial comparing the efficacy of Letrozole and Clomiphene citrate in induction of ovulation in polycystic ovarian syndrome - Kallol Kumar Roy; Jinee Baruah; Shilpa Singla; Jai Bhagwan Sharma; Neeta Singh; Sunesh Kumar Jain; Manu Goyal (Wolters Kluwer Medknow Publications, 2012)
Objectives: To compare the efficacy of letrozole and clomiphene citrate (CC) in patients of anovulatory polycystic ovarian syndrome (PCOS) with infertility. Materials and Methods: This prospective randomized clinical trial included 204 patients of PCOS. 98 patients (294 cycles) received 2.5-5 mg of letrozole; 106 patients (318 cycles) received 50-100 mg of CC (both orally from Days 3-7 of menstrual cycle). The treatment continued for three cycles in both the groups. Main outcome measures: ovulation rate, endometrial thickness, and pregnancy rate. Statistical analysis was done using SPSS 13 software. P value less than 0.05 was considered significant. Results: The mean number of dominant follicles in letrozole groups and CC groups was 1.86±0.26 and 1.92±0.17, respectively (P=0.126). Number of ovulatory cycle in letrozole group was 196 (66.6%) versus 216 (67.9%) in CC group (P=0.712). The mean mid-cycle endometrial thickness was 9.1±0.3 mm in letrozole group and 6.3±1.1 in CC group, which was statistically significant (P=0.014). The mean Estradiol [E2] level in clomiphene citrate group was significantly higher in CC group (364.2±71.4 pg/mL) than letrozole group (248.2± 42.2 pg/mL). 43 patients from the letrozole group (43.8%) and 28 patients from the CC group (26.4%) became pregnant. Conclusion: Letrozole and CC have comparable ovulation rate. The effect of letrozole showed a better endometrial response and pregnancy rate compared with CC.